PERANAN INTERNATIONAL LABOUR ORGANIZATION (ILO) MELALUI INTERNATIONAL PROGRAMME ON THE ELIMINATING OF CHILD LABOUR (IPEC) DALAM MENANGGULANGI PEKERJA ANAK DI INDONESIA - Siti Fijriah Nursiam (Universitas Komputer Indonesia, 2017)
The background of this research is activity of the International Labor Organization (ILO) in the human right especially in Indonesia through the International Program on the Elimination of Child Labor (IPEC) period 2012-2016 as research object. The results of this research are the role of International Labor Organization (ILO) through the International Program on the Elimination of Child Labor (IPEC) to overcome child labor in Indonesia, find the existing programs of the Ansional Action Plan for the Elimination of Child Labor and Forced Work For Children ( RAN-PBPTA); there are also improvements in work performance, child education, hazard training of child laborers, and skills training that is being undertaken in tackling the problem of child labor in Indonesia.